Staphylococcus aureus Small Colony Variants (SCVs): News From a Chronic Prosthetic Joint Infection - Loss, Guilherme; Simões, Patricia Martins; Valour, Florent; Cortês, Marina Farrel; Gonzaga, Luiz; Bergot, Marine; Trouillet-Assant, Sophie; Josse, Jêrome; Diot, Alan; Ricci, Emiliano; Vasconcelos, Ana Tereza; Laurent, Frédéric (Frontiers in Cellular and Infection Microbiology, 2019)
Small colony variants (SCV) of Staphylococcus aureus have been reported as implicated in chronic infections. Here, we investigated the genomic and transcriptomic changes involved in the evolution from a wild-type to a SCV from in a patient with prosthetic joint infection relapse. The SCV presented a stable phenotype with no classical auxotrophy and the emergence of rifampicin resistance. Whole Genome Sequencing (WGS) analysis showed only the loss of a 42.5 kb phage and 3 deletions, among which one targeting the rpoB gene, known to be the target of rifampicin and to be associated to SCV formation in the context of a constitutively active stringent response. Transcriptomic analysis highlighted a specific signature in the SCV strain including a complex, multi-level strategy of survival and adaptation to chronicity within the host including a protection from the inflammatory response, an evasion of the immune response, a constitutively activated stringent response and a scavenging of iron sources.